The Key Molecular Mechanisms of Sini Decoction Plus Ginseng Soup to Rescue Acute Liver Failure: Regulating PPARα to Reduce Hepatocyte Necroptosis? - He Y; Zhang Y; Zhang J; Hu X (Dove Medical Press, 2022)
Ying He,1,2,* Yang Zhang,3,* Junli Zhang,2 Xiaoyu Hu3 1Department of Gastroenterology, Clinical Medical College and the First Affiliated Hospital of Chengdu Medical College, Chengdu, People's Republic of China; 2Department of College of Clinical Medicine, Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China; 3Department of Infectious Disease, Hospital of Chengdu University of Traditional Chinese Medicine, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyu Hu, Department of Infectious Disease, Hospital of Chengdu University of Traditional Chinese Medicine, No. 39 Shi-er-qiao Road, Chengdu, Sichuan Province, People's Republic of China, Tel +86 18981883931, Fax +86 28-87766041, Email xiaoyuhu@aliyun.comPurpose: This study aimed to investigate the improvement effect of Sini Decoction plus Ginseng Soup (SNRS) on the LPS/D-GalN-induced acute liver failure (ALF) mouse model and the molecular mechanism of the SNRS effect.Methods: To study the protective effect of SNRS on ALF mice, the ICR mice were firstly divided into 4 groups: Control group (vehicle-treated), Model group (LPS/D-GalN), SNRS group (LPS/D-GalN+SNRS), and Silymarin group (LPS/D-GalN+Silymarin), the therapeutic drug was administered by gavage 48h, 24h before, and 10 min after LPS/D-GalN injection. On this basis, the peroxisome proliferator-activated receptor (PPAR) α agonist (WY14643) and inhibitor (GW6471) were added to verify whether the therapeutic mechanism of SNRS is related to its promoting effect on PPARα. The animals are grouped as follows: Control group (vehicle-treated), Model group (LPS/D-GalN+DMSO), SNRS group (LPS/D-GalN+SNRS+DMSO), Inhibitor group (LPS/D-GalN+GW6471), Agonist group (LPS/D-GalN+WY14643), and Inhibitor+SNRS group (LPS/D-GalN+GW6471+SNRS).Results: The protective effect of SNRS on the ALF model is mainly reflected in the reduction of serum alanine aminotransaminase (ALT) and aspartate aminotransaminase (AST) as well as the ameliorated pathology of the liver tissue. The survival rate of ALF mice treated with SNRS was significantly increased. Further mechanism studies showed that SNRS significantly promoted the protein expression of PPARα and decreased the expression of necroptosis proteins (RIP3, MLKL, p-MLKL) in ALF mice. Reduced necroptosis resulted in decreased HMGB1 release, which in turn inhibited the activation of TLR4-JNK and NLRP3 inflammasome signaling pathways and the expression of NF-κB protein induced by LPS/D-GalN. The expression of CPT1A, a key enzyme involved in fatty acid β-oxidation, was found to be significantly up-regulated in the SNRS treated group, accompanied by an increased adenosine-triphosphate (ATP) level, which may be the relevant mechanism by which SNRS reduces necroptosis.Conclusion: The potential therapeutic effect of SNRS on ALF may be through promoting the expression of PPARα and increasing the level of ATP in liver tissue, thereby inhibiting necroptosis of hepatocytes, reducing hepatocyte damage, and improving liver function.Keywords: acute liver failure, Sini Decoction plus Ginseng Soup, PPARα, necroptosis, damage-associated molecular patterns, proinflammatory